SHRP 2 C21A: pilot test the ecological approaches to environmental protection developed in capacity research projects C06A and C06B - Lemly, Joanna, author; Goldstein, Joshua, author; Keske, Catherine, author; Smith, Gabrielle, author; Carlson, Erick, author; Anderson, David G., author; Decker, Karin, author; Fink, Michelle, author; Grunau, Lee, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2012)
Awareness of the need for more effective, streamlined, and integrated planning of transportation improvements has permeated all levels of government, and has become a top priority to advance the level of sophistication and integration for transportation planning. For example, the Federal Highways Administration (FHWA) has committed to the use of collaborative approaches to transportation planning, and has established environmental streamlining and stewardship as a major strategic direction for the agency. These approaches are now being recognized for their effectiveness and impact on reduced costs, fewer delays, and better environmental outcomes. Modernized, integrated concepts of transportation planning are the focus of research being supported through the Strategic Highways Research Programs. A significant advancement in this field is the development of the Integrated EcoLogical Framework (referred to hereafter as IEF or Framework) that has resulted from the SHRP 2 CO6 projects. Given the progressive approaches that have been embraced and implemented by the Colorado Department of Transportation (CDOT), such as the Shortgrass Prairie Initiative, the Framework has a strong potential to further advance efforts to insert proactive natural resource conservation into the transportation planning process. At this stage in the evolution of these practices, a process has been developed that holds great promise for improving ecosystem and species recovery and watershed restoration, but it has yet to be adequately tested. This approach represents a major paradigm shift for transportation planning, and before it is (or should be) embraced by the planning community it requires testing, followed, if necessary, by refinements and adjustments. Thus, the Framework, while leading towards better answers and better results, leaves planners with many crucial questions at this juncture. According to the results of C06 research, three main barriers to successful environmental outcomes of transportation projects include lack of resources, lack of data, and resistance to change. CO6 identified three recommended solutions: 1) integrated planning (incorporating transportation, land use, and conservation in practical and effective ways), 2) making data available to support project and planning needs, and 3) the identification of priority conservation areas where opportunities for avoidance, preservation, and restoration can be seized. In this project, the research team addressed all three of these needs, as well as the other questions defined by the research team.
Pilot test the ecological approaches to environmental protection developed in capacity research projects C06A and C06B
At top of each page: Colorado State University: SHRP 2 C21A, April 2012.
August 2012.
Keywords: flat terrain; ranchland; hay meadows; urban centers; highways; transportation planning; mountainous terrain; Colorado